Cost-Benefit Analysis for Industrial Customers-Installed Energy Storage System in South Korea - Lee, Wonjun; Jung, Jaesung; Kang, Byung O. (International Conference on Innovative Smart Grid Technologies, ISGT Asia 2018, 2018)
This paper performs the cost-benefit analysis when the industrial customer installs Energy Storage System (ESS) in South Korea. Firstly, present government's policies and compensation rules for ESS in South Korea are introduced. Then, ESS operation for self-consumption of industrial customers is proposed to maximize the saving of electricity charge with ESS. Actual industry demand profiles are used to verify the effectiveness of the proposed ESS operation and estimate the electricity charge savings. In addition, the cost-benefit analysis is performed to determine if the installation of ESS is beneficial.
Keywords: Arbitrage; Energy storage systems; ESS Exclusive Rate system; Industrial customer; Peak shaving; Self- consumption; South Korea; Arbitrage; Cost-Benefit Analysis; Energy Storage System (ESS); ESS Exclusive Rate system; Peak Shaving